2022
DOI: 10.3389/fphar.2022.870641
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine and Adherence to Medication Therapy Among Stroke Patients: A Meta-analysis and Systematic Review

Abstract: Purpose: To identify the use patterns of complementary and alternative medicine (CAM) and its impact on medication adherence among patients with stroke.Method: A systematic search through Science Direct, Google Scholar, and PubMed was performed to identify potential studies up to June 2021.The primary outcome was CAM use, and the secondary outcome was medication adherence among patients with stroke. Articles included in the review met the following criteria: 1) patients with stroke ≥18 years old on prescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
(156 reference statements)
0
8
1
Order By: Relevance
“…Approximately 85% of respondents stated it is difficult to distinguish legitimate CAIM practices from scams or fraudulent claims. Currently, the evidence base for most CAIM modalities vary greatly in quality [56][57][58][59] . This is partly due to the fundamental differences between CAIM and conventional medicine that make it difficult to study many CAIM therapies under the gold-standard placebo-controlled randomised clinical trial 42,56,57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 85% of respondents stated it is difficult to distinguish legitimate CAIM practices from scams or fraudulent claims. Currently, the evidence base for most CAIM modalities vary greatly in quality [56][57][58][59] . This is partly due to the fundamental differences between CAIM and conventional medicine that make it difficult to study many CAIM therapies under the gold-standard placebo-controlled randomised clinical trial 42,56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…the most positive responses, indicated by over half of respondents cumulatively agreeing that they are promising (n=368, 59.0%) and safe (n=280, 50.3%). Whole medical systems and biofield therapy were less favourable.…”
mentioning
confidence: 99%
“…Currently, balloon dilatation has become a commonly used method for treating post-stroke CPA (Dou et al, 2012 ). Patients suffering from post-stroke CPA can also benefit from acupuncture in terms of swallowing function, and acupuncture has fewer adverse reactions than other treatments (Jia et al, 2009 ; Dou et al, 2013 ; Arnold et al, 2016 ; Han and Gao, 2017 ; Rajahthurai et al, 2022 ). But there is no high-quality evidence for the effect of acupuncture combined with balloon dilation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Rajahthurai et al (2022) showed that the use of complementary medicines in stroke patients is at a low level due to limited knowledge and the high number of medical drugs. [27]. Hashemi et al (2018) introduced the most important barriers to adherence to treatment as the poor performance of the healthcare team, social bottlenecks, and personal helplessness.…”
Section: Discussionmentioning
confidence: 99%